Geo-spatial distribution of serologically detected bovine Foot and Mouth Disease (FMD) serotype outbreaks in Ilesha Baruba, Kwara - Olabode, Hamza Olatunde; Kazeem, Haruna Makajuola; Raji, Moshood Abiola; Ibrahim, Najume Dogongiginya; Nafarnda, Wesley Daniel (Journal of Advanced Veterinary and Animal Research, 2014)
Note: The Corresponding author Hamza Olatunde Olabode was added to the list of authors for this paper on BanglaJOL on 11/11/2015. The PDF was correct. The study was aimed at assessing the prevalence and distribution of bovine Foot and Mouth Disease (FMD) serotypes in Ilesha Baruba, Kwara state-Nigeria. To identify the source of epidemics, geo-spatial analysis was done on the FMD outbreak locations (n=15) using Global Positioning Service (GPS) device (EtrexR). Randomly sampled bovine sera (n=64) from herd representatives were subjected to FMD 3ABC enzyme-linked immunosorbent assay (FMD 3ABC ELISA) and solid-phase competitive ELISA (SP-cELISA), for the screening and serotyping of FMD virus, respectively. Through ELISA, the FMD serotypes detected in this study were- serotype O (83%; n=53/64), serotype A (7.8%; n=5/64), serotype vaccine O (1.6%; n=1/64)), and serotype vaccine SAT2 (1.6%; n=1/64). Multiple serotypes were observed in two different combinations; these were O and A (4.7%; n=3/64), and O and SAT2 (1.6%; n=1/64). FMD multiple serotype infections were associated with absence of cross-immunity between serotypes and cross reactivity enhanced by clustered herds, highland study area topography, road and river interconnectivity, possible human settlements, activities and traffic. This study provides baseline information on geo-spatial distribution, and identification of prevalent FMD serotypes in Ilesha Baruba, Kwara state-Nigeria. DOI: http://dx.doi.org/10.5455/javar.2014.a20 J. Adv. Vet. Anim. Res., 1(3): 94-99, September 2014